The History of Islamic Civilization: A Critical Review of the Thoughts of Ahmad Syalabi and A. Malik Fadjar in the Context of Islamic Education - Arsyada, Aziz Rizqi; Ali, Mohamad; Azani, Mohammad Zakki (Universitas Muhammadiyah Surakarta, 2025)
This paper critically examines the Islamic civilization from two distinctive yet complementary perspectives: Ahmad Syalabi's historical approach and A. Malik Fadjar's educational reorientation framework. Ahmad Syalabi provides a comprehensive historical narrative of Islamic civilization, emphasizing the periodization and cultural achievements of Muslim societies. Meanwhile, A. Malik Fadjar offers a progressive educational paradigm through his concept of